Developing an innovation capital index of global airlines using a hierarchical data envelopment analysis approach - Yu M.-M.; Abdul Rashid A.; See K.F. (Taylor and Francis Ltd., 2023)
Data envelopment analysis; Airline industry; Analysis approach; Business strategy; Geographical locations; Hierarchical data; Innovation capital; International comparison; Multi-dimensional settings; Air transportation